Respostas

2013-06-25T12:01:41-03:00

 x²-6x+7=0

 

Δ=b²-4*a*c

Δ=(-6)²-4*1*7

Δ=36-28

Δ=8

 

x=-b±√Δ 

    2*a

 

x= -(-6)±√8

         2*1

x=6±√4*2

        2

x=6±2√2 = 3±√2

        2

x'= 3+√2

 

x"= 3-√2

 

 S={3+√2 , 3-√2}

3 5 3
  • Usuário do Brainly
2013-06-26T02:56:55-03:00

\text{x}^2-6\text{x}+7=0

 

Temos que:

 

\text{x}=\dfrac{-\text{b}\pm\sqrt{\text{b}^2-4\cdot\text{a}\cdot\text{c}}}{2\cdot\text{a}}

 

Neste caso, \text{a}=1, \text{b}=-6 e \text{c}=7.

 

Observe que:

 

\Delta=(-6)^2-4\cdot1\cdot7=36-28=8

 

Como \Delta>0, a equação possui duas raízes reais distintas.

 

Temos que:

 

\text{x}=\dfrac{-(-6)\pm\sqrt{8}}{2\cdot1}=\dfrac{6\pm2\sqrt{2}}{2}

 

Logo, as raízes são:

 

\text{x}'=\dfrac{6+2\sqrt{2}}{2}=3+\sqrt{2}

 

\text{x}"=\dfrac{6-2\sqrt{2}}{2}=3-\sqrt{2}

 

Portanto, \text{S}=\{3-\sqrt{2}, 3+\sqrt{2}\}.

3 4 3